T‐Type Ca2+ Channels in Cerebral Arteries: Approaches, Hypotheses, and Speculation. (10th May 2013) - Harraz, Osama F.; Welsh, Donald G.
Abstract Cerebral blood flow is controlled by a network of resistance arteries that dilate and constrict to mechanical and chemical stimuli. Vasoactive stimuli influence arterial diameter through alterations in resting membrane potential and the influx of Ca2+ through voltage‐gated Ca2+ channels. Historically, L‐type Ca2+ channels were thought to be solely expressed in cerebral arterial smooth muscle. Recent studies have, however, challenged this perspective, by providing evidence of T‐type Ca2+ channels in vascular tissues. This perspective piece will introduce T‐type Ca2+ channels, their electrophysiological properties, and potential roles in arterial tone development. We begin with a brief overview of Ca2+ channels and a discussion of the approaches used to isolate this elusive conductance. We will then speculate on how the two T‐type Ca2+ channels expressed in cerebral arterial smooth muscle might differentially influence arterial tone. This discovery of T‐type Ca2+ channels alters our traditional understanding of Ca2+ dynamics in vascular tissue and fosters new avenues of research and insight into the basis of arterial tone development.